Multiple, Pan-Enteric Perforation Secondary to Intestinal Tuberculosis - Irfan Masood; Zain Majid; Ali Rafiq; Waqas Rind; Aisha Zia; Sajjad Raza (Case Reports in Surgery)
Free perforation is one of the most feared complications of the intestinal tuberculosis. The terminal ileum is the most common site of perforation, while the majority of (90%) perforations are solitary. Herein, we describe a case of a 25-year-old male who presented with generalized peritonitis requiring an emergency exploratory laparotomy, which revealed pan-enteric perforation characterized by multiple perforations of the small bowel extending 10–15 cm from the DJ flexure up to the terminal ileum. The perforations were primarily closed, while 6–8 cm of the diseased terminal ileum was resected and the two ends were brought out as double-barreled ostomy. To the best of our knowledge, such an extensive tuberculous perforation of the small bowel has not been previously reported in the literature before.